Effect of artificial aging on the surface roughness and microhardness of resin-based materials - Santos, M. Jacinta M.C.; Rêgo, Heleine Maria Chagas [UNESP]; Mukhopadhyay, Anuradha; Najjar, Mai El [UNESP]; Santos, Gildo C. (My University, 2016)
This study sought to verify the effects of aging on the surface roughness (Ra) and microhardness (Knoop hardness number [KHN]) of resin-based restorative materials protected with a surface sealer. Disc specimens of 2 resin-modified glass ionomers (RMGIs) and 1 composite resin (CR) were fabricated in a metal mold. Specimens of each material were divided into 1 group that was covered with surface sealer and 1 group that was not. Both groups of each material were then subdivided according to whether they were stored (aged) in cola or distilled water. Surface roughness and KHN values were obtained from each specimen before and after storage. After aging of the specimens, significantly higher Ra values were observed in the 2 RMGIs when they were not covered with a surface sealer, while the CR was not affected. The KHN values varied by materials and storage conditions (with and without a surface sealer). All the groups with a surface sealer exhibited increased Ra values after aging.